PENGARUH TRUST IN A BRAND DANPERCEIVED VALUE TERHADAP BRAND LOYALTY PONSEL BLACKBERRY - Acoktang Acoktang; Diana Aqmala (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
BlackBerry is a mobile phone made in Canada. BlackBerry was firstintroduced in 1999, and is presented in Indonesia in mid-December 2004. Sinceit was first introduced, the BlackBerrywas much in demand by various groupswith the support of various mobile operators both CDMA and GSM. However,in these days it has decreased significantly. Most users at the end of 2012 asmuch as 79 million active use of BlackBerry mobile phones are recorded. But atthe end of March 2013it decreased as much as 3 million users and it decreasedup to 4 million users at the end of June 2013 who no longer use BlackBerrymobile phone. The final user of BlackBerry mobile phones is 72 million. Thepurpose of this study was to analyze the effect of brand characteristics, companycharacteristics, brand characteristics,and the consumer - perceived benefits to theconsumer brand loyalty on BlackBerry mobile phones in STIE TOTALWINSemarang.The population in this study were students STIE TOTALWINSemarang. Based on Slovin formula, the sample size was 100 respondents thatwere obtained by purposive sampling technique, i.e. students who use BlackBerryphones, at least one month and have experience in using another mobile phone.Primary data was collected through questionnaires and analyzed with multiplelinear regression analysis.The results showed that the Brand Characteristics,Company Characteristics, Consumer-Brand Characteristics and Perceived valuehas significant and positive effect on Brand Loyalty, both partially andsimultaneously. Company Characteristics became the biggest factors influencingbrand loyalty.